Development of Art Activities to Enhance the Social Participation of Children and Youth in the Community: A case study from the Best Practice Community Model - Nuchudom, Tanwarat; Phrompan, Intira (An Online Journal of Education, 2020)
This research aimed to study the development of art activities for the purpose of enhancing social engagement/participation of children and youths in the community. It comprised a case study for the best practice community model. The research samples of this study were three best practice community models, chosen under specific selection criteria; that is, that each was a community model that organized at least three art activities per year. There were three types of informants, which were; 1) three experts in organizing art activities 2) nine community leaders or those who were responsible for organizing art activities within the community, and 3) fifteen children and youths between the ages of 6 and 25 years old. The research instruments of this study were 1) an interview with experts in organizing art activities 2) an interview with community leaders or those who were responsible for organizing art activities within the community 3) an interview with children and youths who participated in provided art activities 4) observation of surroundings and behaviors in art activities involving contribution to social participation of children and youth in the community 5) an interview with community leaders or those who were responsible for organizing the art activities within the community, completed after organizing the activities 6) an interview with children and youths after they participated in provided art activities, and 7) an evaluation form, certified by experts in organizing art activities. The findings of this research were that art activities enhancing social participation of children and youths in the community were initiated by children with the support from adults. Adults and children cooperatively made decision on the art activities. There were 8 activities: 1) art wall 2) sand art 3) Phwng Mhotr paper craft 4) painting fabric bags 5) fabric dying 6) hand puppets 7) moving turbine with love, and 8) growing love pot.